Development of a robust HPTLC method for estimation of β-carotene in nano-formulated apricot extract - Manisha Rajpurohit, Mrityunjaya Patil, Nayeem Khatib (Journal of Applied Pharmaceutical Science, 2025)
Fruits play a crucial role in our fight against diseases and disorders. Apricots are temperate fruits classified under the Rosaceae family. Fruits are rich in carotenoids, phenolic compounds, and flavonoids which contribute to color, taste, and nutritional value. Currently, no standardized high-performance thin-layer chromatography (HPTLC) method exists for analyzing apricots. This study aimed to develop and validate a sensitive, specific, economical, reliable, and precise HPTLC method for quantifying β-carotene in apricot extract and its nano-formulation. Apricot nano-formulation was prepared, characterized, and quantified. In this method, a silica gel aluminum TLC plate was used as the stationary phase, and toluene: acetone in a ratio of 7:3v/v was used as the mobile phase. Analysis was performed at wavelength 448 nm. To ensure method reliability, validation was performed according to ICH guidelines. Prepared nano-formulation showed particle size 101.7 ± 0.12 nm, polydispersity index of 0.125, entrapment efficiency % of 78.6%, zeta potential −25mV, and transmission electron microscopy analysis revealed vesicles are smooth spherical in shape. Regression analysis demonstrated a good linear relationship (R² = 0.9935) within a 100–500 ng/band concentration range. The LOD and LOQ were found to be 22.05 ng/band and 66.82 ng/band, respectively. The validated HPTLC method was successfully applied for quantification of β-carotene in apricot nano-formulation. Hence, the developed HPTLC method would be an important tool in utilizing the quality control methods for herbal formulations.
Keywords: Apricots, β-carotene, high-performance thin layer chromatography, nano-formulation